2018
DOI: 10.1101/328757
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic diversity in twoPlasmodium vivaxprotein ligands for reticulocyte invasion

Abstract: CC) ¶ these authors contributed equally to this work provide unique insights into the roles of these two key ligands by studying the genetic diversity of P. vivax isolates collected from Cambodia, where all individuals are Duffy positive, and Madagascar where both Duffy-positive and Duffy-negative individuals coexists. Our data suggest that PvEBP may play an important functional role in invasion into Duffy-negative reticulocytes. PvEBP appears to be a target of naturally acquired antibody responses following n… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 55 publications
1
17
0
Order By: Relevance
“…We evaluated how the PvDBP sequence polymorphism of the isolates used in the invasion assays affected the response of the parasites to the humabs in order to assess if antigenic variation was responsible for the variations in inhibition observed. Among the 29 isolates used for the in vitro invasion assays, we observed 20 different alleles of DBPII none of which being the Sal1 reference allele, reflecting the known diversity of this gene (Supplementary Table 1) 23 . pvdbp amplification was observed in six of those alleles confirming that this gene amplification is not restricted to a particular parasite genotype ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We evaluated how the PvDBP sequence polymorphism of the isolates used in the invasion assays affected the response of the parasites to the humabs in order to assess if antigenic variation was responsible for the variations in inhibition observed. Among the 29 isolates used for the in vitro invasion assays, we observed 20 different alleles of DBPII none of which being the Sal1 reference allele, reflecting the known diversity of this gene (Supplementary Table 1) 23 . pvdbp amplification was observed in six of those alleles confirming that this gene amplification is not restricted to a particular parasite genotype ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Yet some individuals with high titers of these naturally acquired antibodies remain susceptible to malaria infection and disease suggesting alternative mechanisms to antigenic diversity that the parasite might have evolved to escape this strain-transcending immunity. Recently it was shown that some Pv parasites had two or more copies of the gene coding for PvDBP [21][22][23] . Such Pv isolates were identified from many endemic areas around the world.…”
mentioning
confidence: 99%
“…Although the significance of the expansion of DBP1 is unclear, it suggests the possibility that parasites expressing high levels of DBP1 could infect Duffy-negative erythrocytes expressing a low level of Duffy antigen (leaky expression) in these cells. Alternatively, P. vivax may have evolved to use other invasion pathways relying on ligands other than DBP1 (22,26,27). P. vivax infections in Duffy-positive individuals are generally benign.…”
mentioning
confidence: 99%
“…While we did not detect any formal association between PvDBP copy number and Duffy negativity, it is worth noting that in other parts of the world such as Cambodia, India, and Brazil where only a small proportion of Duffy-negative individuals live, PvDBP expansion was observed with much lower frequency [24]. Although the PvEBP gene was shown to be variable in copy number among the Malagasy P. vivax [42], we detected only a single copy in the Ethiopian P. vivax samples based on whole genome sequences. The functional significance of PvDBP expansion merits further investigations through comparison of gene expression patterns and in-vitro binding assay of varying PvDBP dosage, and study of P. vivax isolates from Duffy negative individuals is clearly a high priority.…”
Section: Discussionmentioning
confidence: 97%